Coin, telephone, and handcuffs: Neural correlates of social knowledge of inanimate objects. (October 2019) - Lin, Nan; Xu, Yangwen; Wang, Xiaoying; Yang, Huichao; Du, Menglin; Hua, Huimin; Li, Xingshan
Abstract: A variety of objects are made to serve social functions. The use of these objects has greatly enriched and expanded our social behaviors. How do our brains represent the social knowledge of inanimate objects such as coins, telephones, and handcuffs? According to a recent version of the grounded theory, social knowledge of inanimate objects might be grounded in the mentalizing network, as the social functions of inanimate objects are closely associated with the intentions of the people using them. However, there is also evidence that the mentalizing network may only get activated when a human/mental agent is detected. Using fMRI, we explored the neural correlates of social knowledge of inanimate objects by comparing the brain activation evoked by high-sociality object nouns (e.g., banknote) with that evoked by low-sociality object nouns (e.g., battery). The left anterior superior temporal sulcus, a classic part of the mentalizing network, showed higher activation for the high-sociality inanimate object nouns than for the low-sociality ones in the whole-brain analysis. Several other areas of the mentalizing network showed sensitivity to object sociality in small volume correction and/or region-of-interest analyses. Our findings indicate that social knowledge of inanimate objects is supported by brain areas in the mentalizing network. Highlights: Brain activations evoked by high- and low-sociality object nouns were compared. Several areas of the mentalizing network showed sensitivity to object sociality. Inanimate social concepts are supported by brain areas in the mentalizing network.